RECIPROCAL TEACHING OF READING TO PROMOTE STUDENTS’ CRITICAL THINKING - Fitri Lestari Sriwahyuni; R. Bunga Febriani; Luthfiyatun Thoyyibah (Universitas Galuh, 2020)
This paper is a case study that aims at finding out the Reciprocal Teaching of Reading to Promote Students’ Critical Thinking. The researchers used a case study in this qualitative research. The research participants of this study were the ninth grade of Islamic Junior High School in Tasikmalaya, consist of twenty five students. In collecting data, the researchers used triangulation method as data collection techniques. The instruments are observation, interview, and questionnaire. The result showed that most of students’ perceptions are good. It is recommended for English teacher to used Reciprocal Teaching in Reading to promote students’ critical thinking.Key words: Reciprocal Teaching, Reading, Students’ Critical Thinking